2023
DOI: 10.1088/1748-605x/ace39c
|View full text |Cite
|
Sign up to set email alerts
|

The role of exosomes in central nervous system tissue regeneration and repair

Abstract: Exosomes are membrane-bound vesicles secreted by various cell types into the extracellular environment, and contain kinds of bioactive molecules. These molecules can mediate various biological processes such as cell differentiation, proliferation, and survival, making them attractive for tissue regeneration and repair. Owing to their nanoscale-size, bilayer membrane structure and receptor-mediated transcytosis, exosomes can cross the blood-brain barrier (BBB) and reach the central nervous system (CNS) tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…In this study, we extracted and identified exosomes from the supernatant and confirmed through cell uptake experiments that extracellular vesicles enter LX2 cells, which could exert important downstream regulatory effects. Exosomes are rich in ncRNAs and proteins, which mediate the functions of multiple cells through various mechanisms 33,34 . Long noncoding RNAs (lncRNAs) have become an important direction in the field of precise regulation due to their cell and tissue specificity 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we extracted and identified exosomes from the supernatant and confirmed through cell uptake experiments that extracellular vesicles enter LX2 cells, which could exert important downstream regulatory effects. Exosomes are rich in ncRNAs and proteins, which mediate the functions of multiple cells through various mechanisms 33,34 . Long noncoding RNAs (lncRNAs) have become an important direction in the field of precise regulation due to their cell and tissue specificity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are rich in ncRNAs and proteins, which mediate the functions of multiple cells through various mechanisms. 33 , 34 Long noncoding RNAs (lncRNAs) have become an important direction in the field of precise regulation due to their cell and tissue specificity. 35 For example, exosomal miR‐192‐5p secreted by bone marrow mesenchymal stem cells inhibits hepatic stellate cell activation and targets protein phosphatase 2‐regulatory subunit 3A (PPP2R3A).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes also serve as pivotal mediators in critical biological processes, including tissue regeneration and development ( Li et al, 2015 ; Pan et al, 2023 ). They orchestrate the process of growth and repair in tissues by facilitating the transfer of growth factors and an array of signaling molecules to target cells ( Wang and Yang, 2023 ; Zhao X et al, 2023 ). In the context of tissue regeneration, exosomes act as specialized messengers, guiding and stimulating cellular responses necessary for the healing and rebuilding of damaged or injured tissues.…”
Section: Generation Of Exosome and Its Functionmentioning
confidence: 99%
“…Exosomal functions have been extensively studied, and the possibility of controlling tissue repair and regeneration is becoming increasingly important; for example, exosomes could be an attractive alternative to numerous cell and tissue engineering techniques 28 . For instance, several investigations of mesenchymal stem cell (MSC) transplantation for tissue regeneration have shown that MSCs primarily alter cells through paracrine signaling mediated by the exosomes they release 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%